Network of national qualifications databases : building trust in skills and qualifications of non-EU countries - (:unkn) unknown (My University, 2024)
"A growing demand for sharing and accessing information on qualifications requires transparency and collaboration between organisations and countries. The ETF has launched the Network of National Qualifications Databases to support countries in the EU's neighbourhood and Central Asia in developing their national databases and allow for comparability of qualifications across countries. This policy briefing provides insights about the role of qualifications databases, why it is crucial to make them interoperable, and the use of existing European tools to support interoperability and information exchange between countries." (Author's absract ; BIBB-Doku)
Keywords: G 1.2.3 Qualifikationsentwicklungen; I 2.2 Europa; I 2.3.4 Asien; 370; 300; EU-Bildungspolitik; Qualifikationsentwicklung; Datenbank; Transparenz; Europa; Mittelasien